ENGLISH SELF-STUDY TECHNIQUES TO IMPROVE SPEAKING SKILLS - Tursunqulova Marjona (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract. The given article illustrates how to improve English speaking skills by self-study.In this article,we will make a discussion various strategies in order to enhance speaking skills.Also,English learners can learn how to do speaking without any aid from peers to develop their skills.The article mainly focuses on cost-effective ways for self-study enthusiasts.The researcher will suggest her own tips and information that she collected.The provided techniques are more suitable for English learners.